Residential Architecture of the XIX Century in Malaga, Europe: Review and Case Study - Assiego-de-Larriva, Rafael (My University, 2019)
This work shows the main characteristics of the vernacular architecture of the XIX century in Malaga. A study about daylight and cross ventilation has been made. Current rules for new buildings have been also studied, the position of the courtyard, clear high between the floor and the roof. Finally, a new building based on old features is showed. The building has seventeen dwelling and is placed on Malaga. As a results of the study is concluded that densification of urban areas and therefore retrofitting of existing heritage in urban settings is one of the key for developed world cities and new building can be designed attended to the new and vernacular rules.
Keywords: Málaga - Arquitectura; City of Malaga; Vernacular architecture; Contemporary design; Daylight; Cross ventilation